Chomskys Universal Grammar: A Case of Its Concepts of Government/Binding Theory - Y.M. Harsono (TEFLIN, 2001)
Abstract: The purpose of this paper is to see the universality of the Government/Binding Theory in its concepts of government, the pro-drop parameter, and binding theory. Three languages Ã¢â¬â English, IndoneÃÂsian, and Javanese Ã¢â¬â are analyzed based on the three concepts. From the analysis it is concluded that in some cases language is universal, but in some other cases every language is specific.